2017
DOI: 10.1038/npp.2017.8
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Lactoferrin Enhances α-Secretase-Dependent Amyloid Precursor Protein Processing via the ERK1/2-CREB and HIF-1α Pathways in an Alzheimer’s Disease Mouse Model

Abstract: Growing evidence suggests that lactoferrin (Lf), an iron-binding glycoprotein, is a pleiotropic functional nutrient. In addition, Lf was recently implicated as a neuroprotective agent. These properties make Lf a valuable therapeutic candidate for the treatment of Alzheimer's disease (AD). However, the mechanisms regulating the physiological roles of Lf in the pathologic condition of AD remain unknown. In the present study, an APPswe/PS1DE9 transgenic mouse model of AD was used. We explored whether intranasal h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 48 publications
5
81
1
Order By: Relevance
“…In fact, it has been reported in the literature that the function of human LF is similar to that of the iron chelator DFO, and it can also induce the neuroprotective effect of hypoxia-inducible factor (HIF-1α) expression under hypoxic conditions ( Kawamata et al, 1993 ). Specifically, our results suggested that LF can enhance the α-secretase-dependent APP process through the ERK1/2-CREB and HIF-1α pathways in vitro and in vivo ( Guo et al, 2017 ), once again proving that LF plays an active role in the treatment of AD. Consistent with previous observations, Aizawa et al (2017) recently reported that the binding of LF to low-density lipoprotein receptor-associated protein-1 (LRP1) leads to the activation of the AMP-activated protein kinase signaling pathway, which in turn, promotes cell autophagy.…”
Section: Iron-targeting Treatment Strategiesmentioning
confidence: 54%
See 2 more Smart Citations
“…In fact, it has been reported in the literature that the function of human LF is similar to that of the iron chelator DFO, and it can also induce the neuroprotective effect of hypoxia-inducible factor (HIF-1α) expression under hypoxic conditions ( Kawamata et al, 1993 ). Specifically, our results suggested that LF can enhance the α-secretase-dependent APP process through the ERK1/2-CREB and HIF-1α pathways in vitro and in vivo ( Guo et al, 2017 ), once again proving that LF plays an active role in the treatment of AD. Consistent with previous observations, Aizawa et al (2017) recently reported that the binding of LF to low-density lipoprotein receptor-associated protein-1 (LRP1) leads to the activation of the AMP-activated protein kinase signaling pathway, which in turn, promotes cell autophagy.…”
Section: Iron-targeting Treatment Strategiesmentioning
confidence: 54%
“…Studies have also shown that an imbalance of metal homeostasis can directly cause neuronal dysfunction ( Myhre et al, 2013 ) and lead to neuronal cell death ( Wright and Baccarelli, 2007 ). Moreover, the successful application of metal (zinc, copper, iron) chelators in several animal models of AD and patients with early AD provided strong evidence that AD is a transition metal-overloading disease ( Guo et al, 2013b , 2015 , 2017 ; Dusek et al, 2016 ; Giampietro et al, 2018 ; Kawahara et al, 2018 ; Zhang et al, 2018 ). Based on the research described above, the metal ion hypothesis was proposed to emphasize the role of metal ions in the pathogenesis of AD, which further complemented the pathogenesis of AD.…”
Section: The Pathogenic Hypothesis Of Alzheimer’s Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Lf is known to be transferred from the sublingual mucosa to the brain [42]. In this context, favourable Lf effects on brain are expected, and they could be related to its antimicrobial capacity but also they may stimulate the non-amyloidogenic processing of APP and the α-secretase catalytic activity and expression in a mouse model of AD [43].…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] These findings suggest that Lf is a suitable ligand to mediate enhanced nose-to-brain delivery of formulations after intranasal administration. [18][19][20] Huperzine A (HupA) is a reversible inhibitor of acetylcholinesterase (AChE) in a club moss (Huperzia serrata), which enhances memory in behavioral animal models. [21][22][23] Studies have shown that HupA exerts multiple neuroprotective effects in addition to inhibition of AChE.…”
Section: Introductionmentioning
confidence: 99%